Marangoni instability of self-rewetting films modulated by chemical reactions flowing down a vertical fibre. (14th December 2020) - Li, Pu; Chao, Youchuang
Highlights: A thin-film model is developed to study the modulation of chemical reactions. Linear stability analysis shows that chemical reactions play diverse roles. The interfacial temperature determines the direction of Marangoni flows. Traveling wave solutions and transient simulations are performed for validation. Abstract: This paper examines the Marangoni instability of a self-rewetting film coating on a vertical heated fibre and its modulation by chemical reactions. A single evolution equation based on the classic thin-film model is derived to study the flow dynamics. Linear stability analysis shows that without chemical reactions, wall heating plays a stabilizing role when T i > T 0 ( T i is the interfacial temperature and T 0 is the temperature corresponding to the minimum of surface tension in self-rewetting fluids), and it plays a destabilizing role when T i < T 0 . However, chemical reactions can strongly modulate how the wall heating affects the flow dynamics. For both situations ( T i > T 0 or T i < T 0 ), the endothermic reaction further enhances respective Marangoni effects, and the exothermic reaction suppresses respective Marangoni effects. In particular, a strong exothermic reaction can totally neutralize and even reverse Marangoni effects. These findings are further confirmed by performing nonlinear traveling wave solutions and transient numerical simulations.